SWIFT: Sweep imaging with FOURIER transformation - Harshavardhan Talla; Vijayalakshmi Nimma; Tejaswi Bathina (Journal of Indian Academy of Oral Medicine and Radiology, 2018)
Oral cavity is prone to a variety of diseases starting from simple tooth decay to life-threatening carcinomas. Injudicious use of ionizing radiation may increase the exposure of a patient and this has been overcome with the use of magnetic resonance imaging. A newer modality sweep imaging with Fourier transform is fast, quiet, and identifies tissues with ultra-short relaxation times. A literature search has been done in main databases such as PubMed and Google Scholar and 20 articles have been included in this review.